2021
DOI: 10.1093/infdis/jiab360
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Frequency and Transmission of HIV-1 Non-B Subtypes Among Men Who Have Sex With Men in the Swiss HIV Cohort Study

Abstract: Background In Switzerland, HIV-1 transmission among men who have sex with men (MSM) has been dominated by subtype B, whilst non-B subtypes are commonly attributed to infections acquired abroad among heterosexuals. Here, we evaluated the temporal trends of non-B subtypes and the characteristics of molecular transmission clusters (MTCs) among MSM. Methods Sociodemographic and clinical data and partial pol sequences were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…However, the epidemic among MSM in Spain is becoming increasingly diverse through the expansion of multiple non-subtype B TCs, comprising or related to viruses circulating in other countries ( González-Domenech et al, 2018 ; Delgado et al, 2019 ). This phenomenon has been also documented in other European countries ( Dauwe et al, 2015 ; Ragonnet-Cronin et al, 2016b ; Verhofstede et al, 2018 ; Fabeni et al, 2019 ; Ramirez et al, 2021 ), where viruses introduced from abroad have expanded successfully among the MSM population.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the epidemic among MSM in Spain is becoming increasingly diverse through the expansion of multiple non-subtype B TCs, comprising or related to viruses circulating in other countries ( González-Domenech et al, 2018 ; Delgado et al, 2019 ). This phenomenon has been also documented in other European countries ( Dauwe et al, 2015 ; Ragonnet-Cronin et al, 2016b ; Verhofstede et al, 2018 ; Fabeni et al, 2019 ; Ramirez et al, 2021 ), where viruses introduced from abroad have expanded successfully among the MSM population.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, almost all the largest TCs (≥30 patients) identified in our study were associated with MSM. HIV-1 molecular epidemiological studies in different countries, independently of the methodology used, have found a similar association ( Parczewski et al, 2017 ; Wertheim et al, 2017 ; Ramirez et al, 2021 ). Also, studies in other Spanish regions have found this association of TCs with MSM ( Pérez-Parra et al, 2015 ; González-Domenech et al, 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…In fact, almost all the largest TCs (≥30 patients) identified in our study were associated with MSM. HIV-1 molecular epidemiological studies in different countries, independently of the methodology used, have found a similar association (Duran-Ramirez et al, 2021;Parczewski et al, 2017;Wertheim et al, 2017). Also, studies in other Spanish regions have found this association of TCs with MSM (González-Domenech et al, 2020;Pérez-Parra et al, 2015).…”
Section: Discussionmentioning
confidence: 64%
“…However, the epidemic among MSM in Spain is becoming increasingly diverse through the expansion of multiple non-subtype B TCs, comprising or related to viruses circulating in other countries (Delgado et al, 2019). This phenomenon has been also documented in other European countries (Dauwe et al, 2015;Duran Ramirez et al, 2021;Fabeni et al, 2019;Ragonnet-Cronin et al, 2016;Verhofstede et al, 2018), where viruses introduced from abroad have expanded successfully among the MSM population.…”
Section: Discussionmentioning
confidence: 93%
“…14,15 The densely sampled drug resistance sequence data base of the Swiss HIV Cohort Study (SHCS) was used in several previous projects to analyze key aspects of the HIV epidemics in Switzerland. 5,6,[16][17][18][19] So far, the drug resistance sequence data base of the Austrian HIV Cohort Study (AHIVCOS) in Austria was not used for a nation-wide phylogenetic analysis to study local transmission patterns, but subsets were used for collaborations. 20,21 Our main aim is to compare transmission dynamics of the local epidemics of Austria and Switzerland, including a quantification of infections occurring outside the country and between these 2 countries.…”
Section: Introductionmentioning
confidence: 99%